2013
DOI: 10.1093/rpd/nct172
|View full text |Cite
|
Sign up to set email alerts
|

Long-term 137Cs activity monitoring of mushrooms in forest ecosystems of the Czech Republic

Abstract: This paper reports on results of activity mass concentration analyses performed in various forest mushrooms in the Czech Republic within 1986 and 2011. The estimated effective half-life of (137)Cs and its environmental half-life (i.e. the effective half-life minus the effect of physical decay) were found to be 5.6 ± 0.6 and 6.9 ± 0.7 y, respectively. Non-homogeneity in (137)Cs surface contamination over the country's territory and fungus species-based (137)Cs accumulation capacity then account for a span of up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…472 based on review results by Calmon et al published in IAEA-TECDOC-1616. After the publication of the handbook, many additional related publications on the fate of 137 Cs in forest ecosystems were published. The data from Chernobyl fallout studies in forests showed that the [ 137 Cs] decreases with time in many different forest compartments such as tree leaves and understory plants. However, that in wild animals such as wild boar and roe deer, [ 137 Cs] remained high for a long time, with seasonal peaks depending on the animals diet. After the Fukushima Dai-ichi accident, T ag values for different components of trees were reported which decreased with time, as expected, due to processes such as the decreasing importance of direct interception of radiocesium and a reduction in the bioavailable fraction in soils. , For wild animals, no information has yet been reported in international literature on the time dependency of T ag for wild animals since the Fukushima Dai-ichi accident.…”
Section: Introductionmentioning
confidence: 99%
“…472 based on review results by Calmon et al published in IAEA-TECDOC-1616. After the publication of the handbook, many additional related publications on the fate of 137 Cs in forest ecosystems were published. The data from Chernobyl fallout studies in forests showed that the [ 137 Cs] decreases with time in many different forest compartments such as tree leaves and understory plants. However, that in wild animals such as wild boar and roe deer, [ 137 Cs] remained high for a long time, with seasonal peaks depending on the animals diet. After the Fukushima Dai-ichi accident, T ag values for different components of trees were reported which decreased with time, as expected, due to processes such as the decreasing importance of direct interception of radiocesium and a reduction in the bioavailable fraction in soils. , For wild animals, no information has yet been reported in international literature on the time dependency of T ag for wild animals since the Fukushima Dai-ichi accident.…”
Section: Introductionmentioning
confidence: 99%
“…The committed effective dose based on mushroom concentration intake was calculated using the following formula: where C is the activity concentration of the detected artificial radionuclide (radiocesium) (Bq/kg), D int is the dose conversion coefficient for adult intake (age 20 and older, 1.3 × 10 −2 µSv/Bq for 137 Cs) ( International Commission on Radiological Protection, 1996 ), and e is the daily intake value (age 20 and older, 5 kg/year, the average intake of Russian citizens) ( Škrkal et al, 2013 ; Malátová& Tecl, 2001 ). We assumed that similar annual intakes could be attributed to each species.…”
Section: Methodsmentioning
confidence: 99%
“…Fungi, as one of the most important constituents of forest ecosystem are capable of accumulating a significant amount of radionuclides including 137 Cs (Heinrich 1991;Škrkal et al 2013;Guillen and Baeza 2014). It is due to their heterotrophic metabolism, significantly different from green plants, and dependence on the supply of final organic compounds (Yoshida and Muramatsu 1994).…”
Section: Mushroom Contaminationmentioning
confidence: 99%